ANALYSIS OF FACTORS AFFECTING FIRM VALUE IN PLANTATION COMPANIES LISTED ON BEI WITH PROFITABILITY AS AN INTERVENING VARIABLE - Margaretha, Christine (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study is to determine and test the factors that affect firm value in plantation companies listed on the Indonesia Stock Exchange and to examine the factors that affect firm value through profitability as an intervening variable. The factors tested in this study are capital structure, liquidity, total asset turnover, inventory turnover, CSR disclosure. This research uses secondary data. The population in this study is plantation companies listed on the IDX. The sample of this research is 10 companies for the period 2012-2016. The analytical tool used in this study is to use multiple linear regression analysis and path analysis with the help of SPSS. Simultaneous analysis results that capital structure, liquidity, total asset turnover, inventory turnover and CSR disclosure and profitability have a significant effect on firm value. Partially, capital structure and liquidity have a negative and significant effect on firm value, total asset turnover has a positive and significant effect on firm value, inventory turnover and CSR disclosure has a negative and not significant effect on firm value. The profitability variable is a significant intervening variable for the total assets turnover and inventory turnover variables to the firm value, and is an insignificant intervening variable in the relationship of capital structure, liquidity and CSR disclosure to the firm value.